Struktur dan Hierarki Ilmu (al-Ghazali dan al-Farabi) - Herman, Muhammad Akbar; M, Marilang; Nonci, Muhammad Hajir (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to understand the meaning of the structure and hierarchy of science, the structure and hierarchy of science according to al-Ghazali, and the structure and hierarchy of science according to al-Farabi. The results of this research show: 1) The structure of science is a systematic collection of knowledge consisting of components that are interrelated or coordinated so that they can become a theoretical basis or provide an explanation. The hierarchy of knowledge is a sequence or level of knowledge; 2) Regarding scientific terminology, Al-Ghazali tries to map it into three global categories based on the level of obligation, source, and social function. In an ontological perspective, Al-Ghazali divides science into Fardhu 'Ain and Fardhu Kifayah. In the epistemological framework, science, according to Al-Ghazali, can be mapped into two, namely Sharia Science and Sharia Ghairu. In Al-Ghazali's reading, all knowledge that is included in the framework of sharia science is commendable. However, this is not the case with knowledge that falls within the domain of sharia-ghiru science. This knowledge is mapped into three domains, namely: praiseworthy, disgraceful, and neutral (mubah); 3) Al-Farabi classified science into two large groups, namely 'Aqliyyah (intellectual) sciences, which were then called Philosophical Sciences, and Naqliyyah (doctrinal) sciences, which were then called Religious Sciences.